2008
DOI: 10.1080/08910600802106517
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism inFibrobacter succinogenes: What NMR tells us

Abstract: Fibrobacter succinogenes is a major rumen fibrolytic bacterium found in high numbers when ruminants are fed cellulose-rich diets. It produces a very efficient fibrolytic system comprising numerous enzymes, but the organization and catalytic features of this system remain unclear. We were using nuclear magnetic resonance (NMR) to study carbohydrate metabolism by Fibrobacter spp. well before the term 'metabolomics' was coined. We first analyzed in detail the NMR spectra arising from resting cells of F. succinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, F. succinogens is known to accumulate large amounts of glycogen, representing up to 60–70% of the dry cell mass (7). A possible explanation for this observation is that the accumulation and degradation of glycogen are separated in time.…”
Section: Discussionmentioning
confidence: 99%
“…However, F. succinogens is known to accumulate large amounts of glycogen, representing up to 60–70% of the dry cell mass (7). A possible explanation for this observation is that the accumulation and degradation of glycogen are separated in time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the complete genome sequence of the strain S85 of F. succinogenes revealed more than 100 predicted enzymes active against plant polysaccharide (Qi et al 2005), suggesting a high potential hydrolytic activity of this organism. The sugar metabolism by F. succinogenes S85 was also extensively investigated (Forano et al 2008), while metabolisation of natural substrates was much less explored. In a previous work, we showed that resting cells of F. succinogenes S85 were able to synthesise and release oligosaccharides identified by 2D-NMR techniques as maltodextrins (MD), maltodextrin-1-phosphate (MD-1P) and another unknown phosphorylated sugar.…”
Section: Introductionmentioning
confidence: 99%
“…For example, F. succinogenes appears to utilise glucose and cellobiose more readily than larger oligosaccharides [22], whereas the converse holds for some other microorganisms [23].…”
Section: Resultsmentioning
confidence: 99%